2021
DOI: 10.1007/s00170-021-06815-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface finishing of hard-to-machine cladding alloys for highly stressed components

Abstract: The supply and processing of materials for highly stressed components are usually cost-intensive. Efforts to achieve cost and resource efficiency lead to more complex structures and contours. Additive manufacturing steps for component repair and production offer significant economic advantages. Machining needs to be coordinated with additive manufacturing steps in a complementary way to produce functional surfaces suitable for the demands. Regarding inhomogeneity and anisotropy of the microstructure and proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
6
20
0
Order By: Relevance
“…Schroepfer et al performed finish milling experiments on AM specimens of IN725 and compared the USAM with the CM. They have found that US causes significantly lower cutting forces compared to CM [19]. Similar results were obtained in investigations of Rinck et al on the influence of ultrasonic assistance on the machinability of Ti-6Al-4 V. Significantly reduced cutting forces due to US compared to CM were observed.…”
Section: Introductionsupporting
confidence: 80%
“…Schroepfer et al performed finish milling experiments on AM specimens of IN725 and compared the USAM with the CM. They have found that US causes significantly lower cutting forces compared to CM [19]. Similar results were obtained in investigations of Rinck et al on the influence of ultrasonic assistance on the machinability of Ti-6Al-4 V. Significantly reduced cutting forces due to US compared to CM were observed.…”
Section: Introductionsupporting
confidence: 80%
“…Wire and arc additive manufacturing (WAAM) is a fast emerging additive manufacturing technique and is utilized for a wide range of materials [11][12][13][14]. The main material focus in research is currently steel, aluminum, and titanium.…”
Section: Wire and Arc Additive Manufacturingmentioning
confidence: 99%
“…These materials are not always of the same chemical composition of the additively manufactured part. Such mixed material joints are commonly known in welding and possible to achieve, e.g., in explosion welding [28,29] or for cladding [14].…”
Section: Wire and Arc Additive Manufacturingmentioning
confidence: 99%
“…Localised heating and uneven cooling during the WAAM process introduce large thermal gradients causing distortion and residual stresses, which can affect the topology and global integrity of a WAAM component [ 3 ]. In the last decade, WAAM induced residual stresses have been experimentally investigated for various alloys, such as steel [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], aluminium [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], titanium [ 3 , 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], nickel [ 13 , 29 , 31 , 32 , 33 ], intermetallics [ 21 , 34 , 35 ], etc. The aforementioned literature has focused on quite a few areas including but not limited to the effect of process and geometrical variables on residual stresses, the effect of interpass and side rolling on controlling/reducing residual stresses, and the effect of pre-and post-processing on residual stresses, etc.…”
Section: Introductionmentioning
confidence: 99%